Processos de desencastelamento patrimonial: Possíveis biografias do Palacete Nhonhô - Pessanha, Lília Márcia de Sousa (Revista do Colóquio, 2023)
This article aims to analyze and discuss the experimental documentary Nhonhô (2020) by visual artists Giselle Beiguelman and Ilê Sartuzi. In the course of the investigations, we sought to understand the motivations that influenced the collection of documentation and archival photographic images and, consequently, the instances summoned when carrying out a re-reading of the history and architectural structure of the mansion of one of the most empowered coffee growers in São Paulo, Nhonhô Magalhães. It is worth mentioning the sensitive impact that it is able to promote in the spectator as a denouncing character of the Brazilian socio-political reality, in which colonial thinking is still in vogue today and cultural treatment is relegated to its dismantling.